Students' Appraisals of their Natural Science Teachers' Performance - Navarro Castro, Hellen (2013)
This paper aims to report some findings about secondary students’ appraisal of their Science teacher’s performance; the displayed results were obtained from the application of two instruments: a) a visit to the classroom, in which three teachers were observed until data saturation was achieved and b) a questionnaire for students of third cycle, in which the respondents indicated their appraisal of their science teachers’ performance in the classroom. The theoretical framework includes topics about the current Educational Policy issued by the Ministry of Education. The methodology is located in the tradition of the naturalistic paradigm, but it includes the collection, analysis and linking of qualitative and quantitative data in the same study. Among the key findings of this research, the relevance of the communication process to achieve good learning stands out along with the importance of having a classroom where respect and cooperation among others prevail.